Maternal sensitivity and the empathic brain: influences of early life maltreatment - Mielke, Emilia Louisa L.; Neukel, Corinne; Bertsch, Katja; Reck, Corinna; Möhler, Eva; Herpertz, Sabine (Journal of psychiatric research, 2016)
One of the most striking characteristics of early life maltreatment (ELM) is the risk of transmission across generations, which could be linked to differences in maternal behavior. Maternal sensitivity includes appropriate and positive affective exchanges between mother and child. Mothers with a history of ELM have been found to show a lower sensitivity representing a significant risk factor for maltreating their own children. 25 mothers with and 28 mothers without sexual and/or physical childhood maltreatment (as assessed with the Childhood Experience of Care and Abuse interview) and their children participated in a standardized mother-child interaction task. Videotaped interactions were rated by two independent trained raters based on the Emotional Availability Scales. In addition, empathic capabilities were assessed with the Interpersonal Reactivity Index. High resolution structural magnetic resonance brain images of the mothers were analyzed with unbiased voxel-based morphometry and correlated with maternal sensitivity. Results indicate that mothers with ELM were less sensitive in the standardized interaction with their own child. In non-maltreated control mothers, maternal sensitivity was positively related to anterior insular grey matter volume, a region which is crucially involved in emotional empathy, while there was a positive association between maternal sensitivity and grey matter volume in parts of the cognitive empathy network such as the superior temporal sulcus and temporal pole region in mothers with ELM. These results implicate that neurostructural alterations associated with poor maternal sensitivity might be a sequelae of ELM and that mothers with ELM may try to compensate deficits in emotional empathy by recruiting brain regions involved in cognitive empathy when interacting with their child. Thus, findings suggest possible coping strategies of mother with ELM to prevent an intergenerational transmission of abuse.
Gesehen am 15.05.2020